The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1752-4458-8-30
|View full text |Cite
|
Sign up to set email alerts
|

The development of mental health services within primary care in India: learning from oral history

Abstract: BackgroundIn India very few of those who need mental health care receive it, despite efforts of the 1982 National Mental Health Programme and its district-level component the District Mental Health Programme (DMHP) to improve mental health care coverage.AimsTo explore and unpack the political, cultural and other historical reasons for the DMHP’s failures and successes since 1947 (post-independence era), which may highlight issues for today’s current primary mental health care policy and programme.MethodsOral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 21 publications
0
78
0
Order By: Relevance
“…The data were collected from the psychiatric outpatient clinic of a private hospital, where the patients were fee paying. Whilst much psychiatric care in India is delivered by private institutions, and the present sample thus represents an important subset of the Indian psychiatric population, the sample was, in general, high‐functioning and the findings are unlikely to be representative of those receiving care from public psychiatric institutions. Within the busy environment of an outpatient clinic, access to collateral information from family and carers was limited, which is extremely useful for a diagnosis of PD.…”
Section: Discussionmentioning
confidence: 91%
“…The data were collected from the psychiatric outpatient clinic of a private hospital, where the patients were fee paying. Whilst much psychiatric care in India is delivered by private institutions, and the present sample thus represents an important subset of the Indian psychiatric population, the sample was, in general, high‐functioning and the findings are unlikely to be representative of those receiving care from public psychiatric institutions. Within the busy environment of an outpatient clinic, access to collateral information from family and carers was limited, which is extremely useful for a diagnosis of PD.…”
Section: Discussionmentioning
confidence: 91%
“…[2] Reviews of the DMHP have been both appreciative and critical. Reviews of the DMHP in 2003,[1] 2009,[18] and 2012[19] concluded that the programme was partially successful at the district level (though not at the primary health-care level) with better awareness of mental illness in implemented districts compared to nonimplemented districts. However, several criticisms have been made of the DMHP which include inadequate leadership at the central, state, and district levels, political neglect, inaccessible funding, and various other administrative and programmatic problems.…”
Section: The Story Of Primary Health Carementioning
confidence: 99%
“…Added to this complexity, there is yet another often cited reason – that as per the Constitution of India, health is a state subject and not under the control of the central government. [1]…”
Section: Introductionmentioning
confidence: 99%
“…Scaling up such programmes or implementation in a national health system is an additional challenge. van Ginneken describes such challenges in an article entitled ' The development of mental health services within primary care in India: Learning from oral histories ' (van Ginneken et al, 2014). Conclusions of van Ginneken ' s work indicate that while capacity is important in scaling up implementation, consistent leadership, policy prioritization and ongoing technical support are also critical elements.…”
Section: Integration Of Behavioural and Medical Care: What Was Old Ismentioning
confidence: 99%